2020
DOI: 10.3390/brainsci10060398
|View full text |Cite
|
Sign up to set email alerts
|

Human Figure Drawings in Children with Autism Spectrum Disorders: A Possible Window on the Inner or the Outer World

Abstract: Background: Tests based on human figure drawings (HFD) have captured the attention of clinicians and psychologists for a long time. The aim of the present study was to evaluate the performance of HFD of children with autism spectrum disorders (ASDs) relative to typically developing (TD) controls. Methods: All children were asked to draw three human figures (man, woman, self-portrait) and were evaluated with a neuropsychological battery. HFD were scored according to the Maturity Scale, and correlative approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…(1) The main media of art therapy include painting, drawing, music, drama, dance, drama, and writing (Chiang et al, 2019). (2) Main contents of painting and drawing include blind drawing, spiral drawing, drawing moods and self-portraits (Legrand et al, 2017;Abbing et al, 2018;Papangelo et al, 2020). (3) Art therapy is mainly used for cancer, depression and anxiety, autism, dementia and cognitive impairment, as these patients are reluctant to express themselves in words (Attard and Larkin, 2016;Deshmukh et al, 2018;Chiang et al, 2019).…”
Section: Overview Of Art Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…(1) The main media of art therapy include painting, drawing, music, drama, dance, drama, and writing (Chiang et al, 2019). (2) Main contents of painting and drawing include blind drawing, spiral drawing, drawing moods and self-portraits (Legrand et al, 2017;Abbing et al, 2018;Papangelo et al, 2020). (3) Art therapy is mainly used for cancer, depression and anxiety, autism, dementia and cognitive impairment, as these patients are reluctant to express themselves in words (Attard and Larkin, 2016;Deshmukh et al, 2018;Chiang et al, 2019).…”
Section: Overview Of Art Therapymentioning
confidence: 99%
“…(3) Art therapy is mainly used for cancer, depression and anxiety, autism, dementia and cognitive impairment, as these patients are reluctant to express themselves in words (Attard and Larkin, 2016;Deshmukh et al, 2018;Chiang et al, 2019). It plays an important role in facilitating engagement when direct verbal interaction becomes difficult, and provides a safe and indirect way to connect oneself with others (Papangelo et al, 2020). Moreover, we found that art therapy has been gradually and successfully used for patients with mental disorders with positive outcomes, mainly reducing suffering from mental symptoms.…”
Section: Overview Of Art Therapymentioning
confidence: 99%
“…(1) The main media of art therapy include painting, drawing, music, drama, dance, drama, and writing (Chiang et al, 2019). ( 2) Main contents of painting and drawing include blind drawing, spiral drawing, drawing moods and self-portraits (Legrand et al, 2017;Abbing et al, 2018;Papangelo et al, 2020). (3) Art therapy is mainly used for cancer, depression and anxiety, autism, dementia and cognitive impairment, as these patients are reluctant to express themselves in words (Attard and Larkin, 2016;Deshmukh et al, 2018;Chiang et al, 2019).…”
Section: Overview Of Art Therapymentioning
confidence: 99%
“…It seems plausible that approaches which consider the communication needs and preferences of autistic children will be more successful in obtaining their perspectives [18]. Further, applying validated non-verbal psychometric assessments, such as projective tests draw on visual communication styles (Draw-A-Person Test [DAPT], [19, 20]) and may be helpful in exploring autistic children’s mental states [21, 22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent meta-analysis findings suggest that emotional self-awareness in school-aged autistic children is comparable to their peers despite the high heterogeneity between the included studies [14]. Furthermore, applying validated non-verbal psychometric measurements, such as projection tests (Draw-A-Person Test [DAPT], [15, 16]), may be conducive to exploring autistic children’s mental states [17, 18, 19].…”
Section: Introductionmentioning
confidence: 99%